تنمية القيم الاجتماعية في الكتاب المدرسي تحليل كتاب اللغة العربية للسنة الثانية من التعليم المتوسط - نصبة, هاجرة; تي, سمية (University of Eloued جامعة الوادي, 2023)
الملخص: هدفت دراستنا إلى التعرف على تنمية القيم الاجتماعية في الكتاب اللغة العربية لسنة ثانيةمن التعليم المتوسط، وحددنا إشكالية الدراسة على النحو التالي: هل أهتم الكتاب المدرسي لسنة ثانية من التعليم المتوسط بتنمية القيم الاجتماعية؟ وتحت هذا التساؤل الرئيسي تندرج التساؤلات الفرعية: هل يساهم الكتاب المدرسي لسنة ثانية من التعليم المتوسط على تنمية القيم الاسرية؟ هل يحتوي الكتاب المدرسي لسنة ثانية من التعليم المتوسط على القيم الوطنية؟ هل احتوى الكتاب المدرسي لسنة ثانية من التعليم المتوسط على القيمة الاخلاقية؟ هل ساهم الكتاب المدرسي لسنة ثانية من التعليم المتوسط على تنمية قيمة البيئية والصحية؟ وللإجابة على هذه التساؤلات اتبعنا منهج الوصفي التحليلي (تحليل محتوى) لدراسة الكتاب اللغة العربية لسنة ثانية من التعليم المتوسط، وتم استخراج (26) قيمة قسمت إلى أربعة قيم رئيسية (قيمة أسرية وقيمة وطنية وقيمة أخلاقية وقيم بيئية وصحية)، وتم بناء استمارة تحليل المحتوى لدراسة وتحليل كتاب اللغة العربية لسنة ثانية من التعليم المتوسط (عينة الدراسة)، وتم استخدام الأساليب الإحصائية التالية: حساب التكرارات والنسب المئوية لتحويل النتائج الكيفية المتحصل عليها إلى نتائج كمية ومناقشتها وتحليلها. وتم التوصل إلى النتائج التالية: ساهم الكتاب المدرسي للغة العربية لسنة ثانية من التعليم المتوسط في تنمية القيم الاجتماعية من خلال ما تم التوصل إليه على أنه ثري بالقيم التالية: كانت القيمة الأولى الأكثر تكرارا هي (قيم الاخلاقية) بنسبة (44.98%)، وتحصلت (قيم الوطنية) على المرتبة الثانية بنسبة (19.76%)، وفي مرتبة الثالثة (قيم الاسرية) بنسبة (18.24%)، وفي المرتبة الاخيرة (قيم صحية و البيئية) بنسبة (17.02%). Résumé :انجلزية Our study aimed at developing the social and moral values in the 2ndyear of middle school Arabic language book. The identification of the research problems are as stated as follows: -Does the Arabic language book of the 2nd middle school year give importance to the social values ? The following sub questions go under the last principal question: -Does the book value the family morals ? -Does the book contain the sense of nationality ? -Does the book signify the moral values ? -Does the contribute in building health and environmental values ? In order to formulate an answer to these questions we followed the analytical, descriptive method (discourse analysis) on the Arabic language book of the 2nd year of the middle school program. After the study was conducted, 26 values were extracted and categorized into four (04) main types (family values, nationality values, moral values, health and environmental values) The content analysis list was structured in order to analyze the Arabic language book of the 2nd class middle school program (the study sample). The following list states the used methods: Calculation of repetitions and percentages to transform the qualitative results into quantitative results, then analyze and discuss them. The research showed the following results: The 2ndyear book of Arabic language from the middle education program contributed in improving the social values from what has been deduced as follows: The 1st and the most frequently repeated values were the moral values with 44.98 %. The nationality values took the 2nd place with 19.78 %. With 18.24 %, family values take place. Finally, the health and environmental values took 17.02 %.
مذكرة ماستر علم الاجتماع تخصص علم اجتماع التربية
Keywords: القيم الإجتماعية، valeurs sociales, Social values; الكتاب المدرسي، livre scolaire, school book